2017
DOI: 10.1097/md.0000000000007432
|View full text |Cite
|
Sign up to set email alerts
|

One-stage surgical treatment of cervical spine fracture-dislocation in patients with ankylosing spondylitis via the combined anterior–posterior approach

Abstract: The aim of the article is to investigate the efficacy and safety of 1-stage surgical therapy via combined anterior–posterior approach on cervical spine fracture in patients with ankylosing spondylitis (AS).We retrospectively analyzed profiles of 12 AS patients with severe fracture-dislocation of cervical spine received 1-stage combined anterior–posterior surgery in our hospital from October, 2013, to October, 2015, including clinical characteristics, follow-up data, and imaging records. We compared the paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Combined surgery can provide strong internal fixation, which allows patients to exercise early for functional recovery and thus reduces the incidence of pulmonary infection associated with long-term bed rest. Although combined approaches are the most invasive option, in cases of ASCF, many studies have shown strong support for this type of treatment [28][29][30][31][32] . This FEM study also found that the combined anterior and posterior approach has the minimal RoM change at the fractured level (C5/6) and the smallest implant MS compared with either approach alone; even 1-level combined fixation provides better stability than 5-level posterior-alone fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Combined surgery can provide strong internal fixation, which allows patients to exercise early for functional recovery and thus reduces the incidence of pulmonary infection associated with long-term bed rest. Although combined approaches are the most invasive option, in cases of ASCF, many studies have shown strong support for this type of treatment [28][29][30][31][32] . This FEM study also found that the combined anterior and posterior approach has the minimal RoM change at the fractured level (C5/6) and the smallest implant MS compared with either approach alone; even 1-level combined fixation provides better stability than 5-level posterior-alone fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of ASIA grades at admission, discharge, and the last follow-up. bined anterior-posterior approach was most commonly used in the cervical spine similar to that of other operative series; 18,[22][23][24] each patient's fracture should be individually assessed for the need for circumferential stabilization. 25,26 In this series, the degree of EDH determined the number of laminectomy levels with the goal of complete decompression of underlying neural elements.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the disadvantage of posterior decompression include progressive deformity and instability of the spine and possibly less recovery of neurological function due to less complete and thorough decompression of the spinal cord 13 . These are strongly appreciated by different studies [14][15] and have been stated that anterior cervical plating has numerous potential benefits as an adjunct to anterior cervical discectomy and fusion (ACDF). It provides rigid fixation, resists graft settling, promotes higher fusion rates, allows less cumbersome external immobilization, and reduce the incidence of graft extrusions.…”
Section: 38mentioning
confidence: 99%